Back Cover: The Cytotoxicity of Layered Black Phosphorus (Chem. Eur. J. 40/2015). Issue 40 (16th September 2015) - Latiff, Naziah Mohamad; Teo, Wei Zhe; Sofer, Zdenek; Fisher, Adrian C.; Pumera, Martin
Abstract : Black phosphorus is a 2D layered material that has attracted interest for its potential uses in optoelectronics, nanoelectronics, and biomedicine. However, little is known about its toxicity. In their Full Paper onpage 13991 ff., M. Pumera et al. discuss their investigations into the cytotoxicity of black phosphorus to human lung carcinoma epithelial cells.